From Hashtag to Policy: Viral Anger and Lawmaking in Indonesia’s Digital Democracy - Ameylia Puspita Rosa Dyah Ayu Arintyas; Savira Aristi; Muhammad Asrul Maulana (Golden Ratio of Law and Social Policy Review, 2026)
This study analyzes how viral digital mobilization translated public anger into policy responses in Indonesia through the 2025 #BubarkanDPR and 17+8 Tuntutan Rakyat movements. While #BubarkanDPR (“Disband the House of Representatives”) emerged as a symbolic critique of legislative privilege and accountability deficits, the 17+8 platform converted diffuse online outrage into twenty-five structured reform demands. Using a qualitative case study integrating digital discourse analysis, media triangulation, and legal document review, the research examines the interaction between emotional mobilization, elite response, and constitutional constraints. The findings demonstrate that viral anger operated as political pressure producing three outcomes: institutional concessions, including suspension of housing allowances and transparency commitments; disciplinary sanctions against legislators after controversial remarks; and activation of oversight mechanisms such as ethics reviews and human rights investigations. However, the core demand to dissolve parliament was constitutionally barred under Article 7C of the amended 1945 Constitution, underscoring structural limits. The study argues that in Indonesia’s digital democracy, virality constitutes contingent political legitimacy, capable of triggering short-term accountability but insufficient to transform entrenched power structures.